Overview of methods and means of implementation of information and measuring components cyber-physical systems for electromagnetic probing - Buchma, Ihor; Voichenko, Mykhailo (Technology audit and production reserves, 2022)
The object of research is cyber-physical systems for the study of inhomogeneous environments, in particular, such as land and water depths, in order to find in them the leading bodies. One of the most problematic places in the creation of such systems is a highly sensitive meter of small phase shifts with a low sensitivity threshold. During the study, a review of methods for achieving a low threshold of sensitivity to phase shift. The main one is the method of converting the phase shift into the amplitude modulation coefficient. The implementation of the method is based on the sum-difference transformation with the preliminary introduction of the quadrature phase shift between the signals. The results concerning the methods of solving the following problems are obtained: – increasing the temperature stability of the quadrature phase shifter; – reducing the non-identity of the transmission coefficients of the sumo-difference scheme channels; – allocation of the amplitude of the amplitude-phase-modulated signal at low ratios of the frequencies of the input signals and switching. The first problem is partially solved by dividing the quadrature phase shifter into two equal halves, placed in different channels, with approximately the same phase temperature coefficients. The second problem is also solved by manual calibration before measurement. The most difficult task is to extract the bypass from the amplitude-phase-modulated signal, in which the carrier frequency is only several times greater than the bypass. The difficulty is that the detection produces combinational frequencies due to phase modulation. Therefore, it is difficult to separate them. Several methods of allocating the bypass, if the frequency of the input signals is fixed, are considered. This allows to get the sensitivity threshold (1·10–4÷3·10–5) of advice. Reducing the operating frequency of the signals increases the depth of research, but increases the impact of flicker noise. The minimum frequency is 10 Hz. Therefore, these methods are not suitable for frequencies of Hz units. Methods to reduce the impact of flicker noise will be considered in another paper.